Evaluasi Degradasi dan Performa Panel Surya Multikristal di Kondisi Iklim Tropis dengan Translasi IEC 60891 - Assalam, Imam Faried; Muhammad, Umar; Irvawansyah, Irvawansyah (Joule (Journal of Electrical Engineering)., 2024)
Every year, solar panels experience a decline in production, so it is necessary to evaluate the degradation and performance of multicrystalline silicon (mc-Si) solar panels in tropical climate conditions. This research uses SEAWARD PV 200 (Complete Kit) to measure solar panel output data, which is then analyzed using the translation method according to IEC 60891 Procedure 1 to determine Standard Test Conditions (STC). The translational results showed a solar panel degradation rate of ±1.16% per year. Performance evaluation using the linear regression method revealed that a tropical climate that increases the temperature of the solar panel increases the percentage of degradation, where every 1°C increase in temperature causes an increase in degradation of approximately ±0.15%.